1983
DOI: 10.1161/01.str.14.4.511
|View full text |Cite
|
Sign up to set email alerts
|

Platelet function tests in thrombotic cerebrovascular disorders.

Abstract: A variety of platelet function tests were performed in patients with four forms of obstructive cerebrovascular disease (CVD); transient ischemic attacks (TIA), reversible ischemic neurological deficit (RIND), cerebral infarct, and cerebral embolism of cardiac source in rheumatic valvular heart disease (RVHD). Platelet studies included platelet aggregation induced by ADP and ristocetin, spontaneous platelet aggregation, von Willebrand factor (VIII:vWF), platelet aggregation enhancing factor (PAEF), and percenta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
31
0

Year Published

1985
1985
1999
1999

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 82 publications
(31 citation statements)
references
References 29 publications
0
31
0
Order By: Relevance
“…5 Other authors have found no such correlation in healthy subjects later suffering cardiovascular events. 6 - 27 Uchiyama et al 28 found increased vWF:Ag levels in patients with thromboembolic but not embolic (rheumatic valvular heart disease) stroke.…”
Section: Discussionmentioning
confidence: 99%
“…5 Other authors have found no such correlation in healthy subjects later suffering cardiovascular events. 6 - 27 Uchiyama et al 28 found increased vWF:Ag levels in patients with thromboembolic but not embolic (rheumatic valvular heart disease) stroke.…”
Section: Discussionmentioning
confidence: 99%
“…Although a number of studies have investigated the association of platelet activation with MI 10,11 and stroke, 7,8,24 the majority have been relatively small. Elevated levels of ␤-TG have been found in subjects with thromboembolic and cardioembolic stroke compared with those with small-vessel infarction and healthy control subjects 7 ; similarly Konstantopoulos et al 8 found increased shear-induced platelet aggregation and a persistent increase in the percentage of circulating activated platelets in subjects with large-vessel infarction compared with those with small-vessel infarction or control subjects.…”
Section: Markers Of Platelet Activation In Relation To Stroke Strokementioning
confidence: 99%
“…Increased ADP-induced platelet aggregation and increased spontaneous platelet aggregation have also been found in subjects with transient ischemic attack or reversible ischemic neurologic deficit and cerebral infarction compared with healthy controls. 24 In the Caerphilly Collaborative Heart Disease Study, hypersensitivity to ADP was found in subjects with a past history of MI or ECG evidence of ischemic heart disease. 10 …”
Section: Markers Of Platelet Activation In Relation To Stroke Strokementioning
confidence: 99%
“…[3][4][5] Platelet activation results in a conformational change in the glycoprotein (GP) IIb/IIIa receptors on the platelet surface, which facilitates binding of soluble fibrinogen and platelet aggregation. 6 GPIIb/IIIa (␣ IIb ␤ 3 ) is a member of the integrin family of cell adhesion molecules, 7 and its importance in the pathogenesis of cardiovascular disease has been highlighted by the clinical use of anti-GPIIb/IIIa agents.…”
mentioning
confidence: 99%